Reversible Electrochemical Silver Deposition over Large Areas for Smart Windows and Information Display. (20th November 2017) - Rai, Varun; Tiwari, Naveen; Rajput, Mayank; Joshi, Salil M.; Nguyen, Anh Chien; Mathews, Nripan
Graphical abstract: Highlights: Scaling up of silver based reversible electrodeposited system for large area smart window applications. Studied the role of the redox mediator in improving switching time and transparency of EC devices. Demonstrated reversible flexible electrochromic devices (active area 2.5 × 2.5 cm 2 ). Through very simple patterning strategies, large area information display and decorative patterns are demonstrated and assembled over large sheet of ITO. Abstract: Silver based reversible electrochromic (EC) devices which can be used for smart windows and information display are analysed to examine the factors that determine switching time, color, and scale-up. These devices demonstrate multiple colors: silver, black, magenta, yellow and dark cyan blue with switching time as low as 5 seconds. The usage of redox mediators, applied bias, in enhancing the kinetics of the color transformation while being constrained by the electrochemical window of the DMSO solvent was examined. By a judicious combination of these factors, fabrication of large-area electrochromic devices up to 77 cm 2 operating at −3.0 V for formation of mirror-like reflective state (∼100% reflectance) in less than 15 seconds; and reverse switching to transparency at 0.5 V in less than 30 seconds have been realised. Devices capable of transforming into different patterns are also demonstrated with similar switching performance.